Kajian Struktur Dan Mekanisme Senyawa Aktif Kayu Manis Sebagai Terapi Alternatif Diabetes Melitus: Tinjauan Kimia Medisinal - Saeful Amin; Jelin Mutiara Guswara; Widiya Zulvania; Adisti Rahma (Jurnal Sains dan Ilmu Terapan, 2025)
Diabetes mellitus is a chronic metabolic disease characterised by hyperglycaemia due to impaired insulin secretion or action. Conventional therapies often cause side effects and limited long-term efficacy, thus encouraging the exploration of alternative therapies based on natural compounds. Cinnamon (Cinnamomum spp.) has been empirically known to have antidiabetic effects, mainly through the content of bioactive compounds such as cinnamaldehyde, eugenol, cinnamic acid, coumarin, and proanthocyanidin.